Photodegradation of Eosin Yellow Dye in Water under Simulated Solar Light Irradiation Using La–Doped ZnO Nanostructure Decorated on Graphene Oxide as an Advanced Photocatalyst. Issue 4 (29th January 2018) - Oppong, Samuel Osei‐Bonsu; Anku, William Wilson; Opoku, Francis; Shukla, Sudheesh Kumar; Govender, Penny Poomani
Abstract: Organic pollutants from the industries and anthropogenic sources pose severe problems to both the environment and human health. Hence, there is the need to eliminate these pollutants from our water bodies, as safe drinking water is a major prerequisite for healthy life and also as precious resources for human civilisation. In this study, a photocatalyst (La‐ZnO‐GO) with improved photocatalytic properties is synthesised using co‐precipitation approach. The photocatalytic activities, morphologies and structures of the photocatalyst are investigated by means of advanced technologies such as Ultraviolet‐Visible spectroscopy, X‐ray diffraction, Raman spectroscopy, transmission electron microscopy, scanning electron microscopy. Under visible light irradiation, Eosin Yellow (EY) dye was used to calculate the photocatalytic behaviour of La‐ZnO‐GO composite. The photocatalytic outcome shows that the 0.3% La‐ZnO‐GO photocatalyst displayed a better photoactivity towards the degradation of organic pollutant. This effective photodegradation of EY dye solution is ascribed to the mutual effect of La and graphene oxide, as well as the improved visible light absorbance and the separation of electron‐hole pairs. The total organic carbon result shows a significant mineralisation of EY dye, which drops the formation of potentially harmful degradation by‐products. The stability results show a recyclability of the 0.3% La‐ZnO‐GO composites with 89% degradation efficiency after the five (5) cycles. Abstract : A La‐ZnO‐GO nanocomposite photocatalyst towards Eosin Yellow dye was synthesised using co‐precipitation approach for the first time. The as‐prepared nanocomposite showed photoactivity towards Eosin Yellow dye with 89% degradation efficiency after the five (5) cycles. A significant mineralisation of Eosin Yellow dye was observed from the total organic carbon result.